Metodología para la estimación preliminar de la curva de desempeño de una turbina darrieus hidrocinética “h” (2021)
One of the most used ways today to estimate the efficiency of a kinetic exploitation turbine (wind or hydraulic), is through the analysis of Computational Fluid Dynamics - CFD, which allows studies case with results very close to the real ones; However, determining the performance characteristics through the numerical resolution of the CFD equations entails a high computational cost. To obtain a good preliminary approximation of the power coefficient for Darrieus “H” type hydrokinetic turbines with a lower computational cost, this work proposes an analytical methodology based on the solution of the integral Glauert equation. This methodology allows a priori comparison, the variation in the efficiency of the Darrieus H turbine rotor as a function of the progressive change in its solidity, thus making it possible to discriminate the number of configurations to be tested in subsequent CFD or experimental analyzes, necessary for the more detailed design of this type of turbines.